Growth hormone inhibition causes increased selenium levels in Duchenne muscular dystrophy: a possible new approach to therapy. Issue 4 (August 1984) - Collipp, P J; Kelemen, J; Chen, S Y; Castro-Magana, M; Angulo, M; Derenoncourt, A
Abstract : Nine children with Duchenne muscular dystrophy were given Sanorex (mazindol), a growth hormone inhibitor, daily for 6 months. There was no significant change in their muscle function, but there was a significant reduction in weight gain and in levels of growth hormone, somatomedin C, hair zinc, serum zinc, and serum LDH. Selenium and glutathione peroxidase in the serum increased significantly. Thirteen other children with growth hormone deficiency had a significant reduction in hair selenium following growth hormone administration. These results show a significant relationship between growth hormone and selenium nutritional status and confirm our previous reports indicating an effect of growth hormone on zinc nutritional status. It is possible that prolonged therapy with a growth hormone inhibitor would attenuate the course and improve the longevity of patients with muscular dystrophy.